Locus Of Control, Work Stress And Work Conflict On The Performance Of Bpjs Health Employees In The Padang Branch - Elana Fitriani; Harif Amali Rivai; Laura Syahrul (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the effect of locus of control, work stress and work conflict on the performance of BPJS Kesehatan Padang Branch employees. The most important managerial role is in human resources. Humans can be seen as the determining factor, because in the hands of humans all innovations will be realized in an effort to realize the company's goals. The type of research used in this research is quantitative research with the help of a questionnaire, where the respondents are employees of BPJS Kesehatan Padang Branch with a working position as company staff and including the head of the field, totaling 83 respondents. The analytical method used is descriptive statistical analysis and factor description analysis using SmartPLS 3.0 software. The results showed that locus of control had a significant and positive effect on employee performance; work stress has a significant and positive effect on employee performance; work conflict has a negative and insignificant effect on employee performance.